Treatment options for methicillin-resistant Staphylococcus aureus (MRSA) infection: Where are we now?. Issue 3 (September 2014) - Edwards, B.; Andini, R.; Esposito, S.; Grossi, P.; Lew, D.; Mazzei, T.; Novelli, A.; Soriano, A.; Gould, I.M.
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) infection continues to be a substantial global problem with significant associated morbidity and mortality. This review summarises the discussions that took place at the 4th MRSA Consensus Conference in relation to the current treatment options for serious MRSA infections and how to optimise whichever therapy is embarked upon. It highlights the many challenges faced by both the laboratory and clinicians in the diagnosis and treatment of MRSA infections.